Economic geology of the refractory clays in the Union of South Africa with particular reference to the Transvaal deposits - Warde, John M; Warde, John M (Department of Geological Sciences, 2017)
The purpose of this thesis is to describe the occurrence, nature, properties, and utilization of the refractory clays in South Africa with particular reference to the Transvaal deposits, focusing on those characteristics which may be of direct value in the future development of this important mineral resource. Principal attention has been devoted to producing areas and-generally confined to those materials used in the production of fire-clay refractories; however, in many cases these identical clays are employed in the manufacture of "golden brown" building brick, sewer pipe, earthenware, etc. A fundamental study of the constitution of the commercial refractory clays was carried out on selected samples obtained from operating workings. The differential thermal method of analysis was featured in these studies, supple mented by X-ray examination and other recognized determinative procedures. The basic data so obtained were correlated, where possible, with the ceramic properties of the clays in order to lead to a better understanding of the relationship between the refractory clays and the ware made from them.